The COVID-19 pandemic and the state in Bihar - Avinash Kumar; Manish Kumar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper presents a critical analysis of official data related to COVID-19 in Bihar state, India, which points to the manipulation of data for political ends. The ruling party's claim that the state managed the COVID pandemic brilliantly seems more politically motivated than scientific. We show that during both the first and the second waves of COVID-19 in Bihar, the state government failed to provide relief to its people and left many of them, particularly the poor, without food, health care, or transport for weeks and months while it successfully negotiated its own re-election.
Keywords: I18; H75; 330; manipulation of data; COVID pandemic; Bihar; health; COVID-19